An examination of the validity of the education participation scale (EPS) and the adult attitudes toward continuing education scale (AACES) - Adrian Blunt; Baiyin Yang (Adult Education Research Conference, 1995)
Confirmatory factor analysis and structural equation modeling, with LISREL as the estimation technique, were used to assess the validity of the Education Participation Scale (EPS) and the Adult Attitudes Toward Continuing Education Scale (AACES). Results of the analyses revealed: 1) the six factor structure of the EPS to be reproducible and the three factor structure of the AACES to be weak and poorly determined, 2) acceptable levels of convergent and concurrent validity for the EPS and a revised version of the AACES, 3) weak evidence of discriminant validity for each scale, and 4) poor predictive validity for both scales.